Symbolic semantics in philosophy and anthropology - Mansoor, Jameel Mohsin (International Journal of Psychosocial Rehabilitation, 2020)
Symbolism is a crucial part of social heritage including cultural, religious and scientific levels. However, the social anthropology cannot give up the use of symbolism due to its importance in day to day life. The paper clarifies that symbolism is a significant part of social development in all fields including anthropology. The language used by people; it merely consists of a system of symbols. Therefore, symbolism has become a means to express the status of man’s life. The paper refers to many and various cases and supply examples from certain communities which proves that symbolism is an essential part of these communities but it is not intrusive. The research consists of five sections; the first discusses scholars’ opinions man’s social history and how social interaction had a positive effect in developing communities via using language. The second section deals with the interaction between symbolism and anthropology in which symbolism is indispensible for anthropology. The third section concerns with the process of symbols interpretation within social setting. The fourth section tackles how symbolism has become a crucial part in social and cultural structure in any society in the past and the present. Finally, the research is ends up with conclusion which recapitulates the main points of the paper.